Influence of hydrogen plasma thermal treatment on the properties of ZnO:Al thin films prepared by dc magnetron sputtering - Castro, Maria Freire Flores Vieira (2014)
ZnO:Al transparent and electrically conductive thin films were deposited on glass surfaces by d.c. pulsed magnetron sputtering from an AZOY (ZnO ¼ 97.88 mol%, Al2O3 ¼ 2 mol%, Y2O3 ¼ 0.12 mol%) target. In order to study the influence of sputtering pressure on the optical and electrical properties of the asdeposited thin films, different argon flow rates were used for deposition. It is shown that a lower argon pressure leads to lower film electrical resistivity. The influence of different annealing temperatures (between 473 and 723 K) performed at different pressures (0.5, 8.0, 46.7 and 120 Pa), on the final electrical, optical and structural properties of the films, was investigated. An electrical resistivity of w1.2 10 3 U cm and a transmittance of w80% in the visible region for thickness of w200 nm was achieved for samples submitted to a one hour hydrogen plasma treatment with a working pressure of 0.5 Pa at a temperature of 623 K. This treatment proved to be a very efficient in enhancing the electrical properties of these films. Concerning the thermoelectric properties, a maximum power factor of 7.27 10 5 W/mK2 was obtained at 350 K for the sample deposited with the lowest sputtering pressure (0.37 Pa).